Strategic improving of teachers competence junior high schools in Bandung regency - Sutarman (Linguistics and Culture Review, 2021)
This study aims to determine the competence of teachers (1). Pedagogy (2). Personality (3). Social competence (4). Professional competence. The research method with a qualitative approach describes events and phenomena that occur in the field. Data collection techniques through interviews with the main volunteers, site surveys, documentation studies and literature studies. Conclusion: (a). Develop strategic planning (b). Strategic implementation in accordance with the agreed plan (d). Strategic evaluation is carried out routinely, measuring all activities and providing an assessment.